Using Voice Over (VO) in Creating Materials for Teaching Speaking Skills - Fitria, Tira Nur (English Education Department, Postgraduate, Universitas Sultan Ageng Tirtayasa, Indonesia, 2024)
This research describes the use of Voice Over (VO) techniques in creating teaching materials for teaching speaking skills. This research is descriptive qualitative. The analysis shows that Voice Over (VO) technique in teaching English Speaking encompasses a broad range of contexts to focus on language proficiency and practical communication skills. This prepares students to navigate diverse real-life interactions encountered in daily life. Teachers utilize VO techniques to narrate dialogues and narratives, introduce vocabulary, and enhance pronunciation and intonation skills. They can separate recordings to focus on skill development and integrate learning into everyday contexts, grammar explanations, and create immersive experiences. They can use user-friendly voice recording software, produce interesting/engaging content, boost confidence, and improve communication skills. VO teachers should master pronunciation, intonation, and communication through regular vocal practice, and adapt their teaching to meet students' needs by adjusting language levels and providing constructive feedback for continuous improvement. They can employ creative methods like storytelling and role-playing to train speaking abilities, thereby fostering interactive learning and dynamic educational environments. When creating VO materials, teachers begin by selecting interesting/engaging topics such as everyday conversations or professional scenarios. They meticulously script clear and structured dialogues, instructions, or narrations with appropriate vocabulary to meet specific learning objectives. They should ensure high-quality audio recordings with clear pronunciation by native speakers to maintain authenticity and minimize distractions while integrating multimedia elements to enrich the learning experience and reinforce comprehension. Specific examples of VO materials can be found in daily activity and real life which illustrate utility in providing practical language learning experiences.